Effects of hydrothermal treatment and pelletizing temperature on physical properties of empty fruit bunch pellets. (February 2019) - Ruksathamcharoen, Sirawasith; Chuenyam, Teerapong; Stratong-on, Pimpet; Hosoda, Hideki; Sesillia, Tri; Yoshikawa, Kunio
Abstract: Palm empty fruit bunch (EFB) has a high potential to be utilized as energy source in Indonesia. However, due to some of its properties such as low bulk density, low hydrophobicity, high moisture content, high chlorine and alkaline content, pretreatment of EFB is required before it can be utilized as fuel. This study examined the effects of hydrothermal treatment and pelleting temperature on physical characteristics of EFB pellets. EFB was hydrothermally treated using 10m 3 batch type reactor and water leached using centrifugal machine. Single pellet making device was used for densification of both treated and untreated EFB. Pellets were compacted at a pressure of 60 MPa and temperature of 100, 150 and 200 °C. Pellet density, compressive strength and durability of each pellets were evaluated. Results indicated that combination of hydrothermal treatment and water leaching significantly improved pelletization performance of EFB especially when it was pelletized at 100 °C. At pelleting temperature of 100 °C, pellet durability index (PDI) and compressive strength of EFB increased from 78.1% and 2.85 MPa to 98.72% and 7.80 MPa respectively when it was hydrothermally treated. Notable increase in pellet properties of untreated EFB were also observed as pelletizing temperature increase. At pelleting temperature of 200 °C, PDI and compressive strength increased to 92.83% and 7.09 MPa respectively. However, only slight improvement in characteristics of the washed hydrochar pellets were observed as the pelletizing temperature increased.